Air Distribution in a Fully-Closed Higher Plant Growth Chamber Impacts Crop Performance of Hydroponically-Grown Lettuce - Peiro, Enrique; Pannico, Antonio; Colleoni, Sebastian George; Bucchieri, Lorenzo; Rouphael, Youssef; De Pascale, Stefania; Paradiso, Roberta; Gòdia, Francesc (Frontiers in Plant Science, 2020)
The MELiSSA Pilot Plant (MPP) is testing in terrestrial conditions regenerative life support technologies for human exploration in Space. One of its components is a controlled Higher Plant Chamber (HPC) accommodating hydroponic plant cultures. It consists of a 9 m3 single closed growth chamber providing adequate environmental conditions for growing plants, enabling the production of food, water and oxygen for the crew. A critical aspect for a reliable HPC performance is to achieve homogeneous air distribution. The initial experiment carried out in the MPP with lettuce as salad crop, showed uneven plant growth throughout the HPC, which was attributed to inadequate air distribution due to non-homogeneous air velocity profile along the inlet-vents. After a detailed computational fluid dynamics (CFD) analysis, the heating, ventilation, and air conditioning subsystem of the HPC was upgraded and a new experiment was carried out in optimized air flow conditions. Nine-day seedlings of lettuce cultivar “Grand Rapids” were transplanted into the HPC and harvested at the end of the growing cycle, where shoot fresh weight, dry biomass, and shoot mineral composition were analyzed. During the experiment, the environmental control system performed remarkably well based on the biometric measurements as well as the mineral composition leading to a vast homogeneous growth. Overall, the results demonstrated the beneficial effect of an adequate air distribution system in HPCs and the effectiveness of CFD-analysis to design properly the gas distribution. The obtained results are of high relevance for life support systems in space involving plants growth.